FRI0602 SERUM ALBUMIN PREDICTS ONCOLOGICAL OUTCOMES BUT NOT RHEUMATIC IMMUNE-RELATED ADVERSE EVENTS FOLLOWING PD-1 INHIBITOR THERAPY. (June 2019) - Mcmaster, Christopher; Liew, David; Liu, Bonnia; Leung, Jessica; Frauman, Albert; Cebon, Jonathan; Buchanan, Russell
Abstract : Background: Rheumatic immune-related adverse events (irAEs) following immune checkpoint inhibitor (ICI) therapy for cancer are an increasing burden on rheumatological services but have also been associated with subsequent good oncological outcomes(1). A clinical need for biomarkers to predict rheumatic irAEs exists. High serum albumin and low lactate dehydrogenase (LDH)(2) prior to ICI therapy has been associated with subsequent good oncological outcomes, and may therefore predict rheumatic irAEs, but to the best of our knowledge this has not previously been examined. Objectives: To determine the relationship between serum albumin and LDH of immune-related adverse events (irAEs) and oncological outcomes following treatment with the main classes of ICI therapy for cancer, programmed cell death protein 1 (PD-1) inhibitors and programmed death-ligand 1 (PD-L1) inhibitors. Methods: We retrospectively examined all patients at a single centre who had a serum albumin performed in the institutional laboratory before treatment with a PD-1 or PD-L1 inhibitor before January 1, 2018, with follow-up until October 1, 2018. Patients with any diagnosis of a rheumatic irAE were identified. Treatment response was determined based on assessment by the treating oncologist, with favourable oncological response defined as complete or partial response. Statistical tests were performed using two-tail t-tests. Missing laboratory values were imputed using median imputation. Results: There were 401 episodes of therapy which met criteria, of which 324 had a serum albumin level and 244 had serum LDH prior to the commencement of therapy. A rheumatic irAE was diagnosed in 26 of the 401 patients (6.5%) and a good oncological response was noted in 140 patients (34.9%). There was a statistically significant relationship between higher baseline serum albumin and favourable oncological response (p < 0.001), but not with the development of a rheumatic irAE (p=0.41)(Table 1 ). Although serum LDH levels were lower in those with favourable oncological response, this relationship was not statistically significant (p=0.16). Similarly, LDH levels were lower on average in those who subsequently developed a rheumatic irAE, however this relationship was not statistically significant (p=0.57). Conclusion: High serum albumin was associated with good oncological outcomes following ICI therapy with a PD-1 or PD-L1, but not with rheumatic irAEs. The reason for this dissonance is not clear. Not all markers of good oncological response predict rheumatic irAEs and further study should focus on consequent implications for rheumatic irAE pathophysiology. References: [1] Kostine M, Rouxel L, Barnetche T, Veillon R, Martin F, Dutriaux C, et al. Rheumatic disorders associated with immune checkpoint inhibitors in patients with cancer-clinical aspects and relationship with tumour response: a single-centre prospective cohort study. Ann Rheum Dis. 2017. [2] Bigot F, Castanon E, Baldini C, Hollebecque A, Carmona A, Postel-Vinay S, et al. Prospective validation of a prognostic score for patients in immunotherapy phase I trials: The Gustave Roussy Immune Score (GRIm-Score). European Journal of Cancer. 2017;84:212-8. Disclosure of Interests: None declared